1999
DOI: 10.1086/515102
|View full text |Cite
|
Sign up to set email alerts
|

Cat‐Scratch Disease with Paravertebral Mass and Osteomyelitis

Abstract: The case of a 9-year-old girl with cat-scratch disease (CSD) complicated by development of a paravertebral mass and osteomyelitis is presented. Following multiple scratches and inguinal lymphadenopathy, she developed back pain, and imaging demonstrated a paravertebral mass with evidence of osteomyelitis involving vertebra T9. The diagnosis was made on the basis of detection of Bartonella henselae by use of molecular techniques on an aspirate from the vertebral column and supportive serology for infection with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 18 publications
1
29
1
Order By: Relevance
“…B. henselae serology and PCR are very useful current tools to confirm CSD osteomyelitis. Serology was positive in most of the CSD osteomyelitis cases (13,14,18,21). Serology in our case was done by indirect immunofluorescence, and the cutoff values for positive serology were at a dilution of 1/128 for IgG and of 1/64 for IgM (7).…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…B. henselae serology and PCR are very useful current tools to confirm CSD osteomyelitis. Serology was positive in most of the CSD osteomyelitis cases (13,14,18,21). Serology in our case was done by indirect immunofluorescence, and the cutoff values for positive serology were at a dilution of 1/128 for IgG and of 1/64 for IgM (7).…”
mentioning
confidence: 74%
“…Serology in our case was done by indirect immunofluorescence, and the cutoff values for positive serology were at a dilution of 1/128 for IgG and of 1/64 for IgM (7). Positive PCR has been reported in only two lymph nodes and in six osseous tissues of CSD osteomyelitis (6,10,13,14,17,18,21). In our case, we tested both the osseous and the lymph node materials.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Patients with osteomyelitis attributed to cat scratch disease have been successfully treated with erythromycin, azithromycin, rifampin, tetracycline, and gentamicin either alone or in combination (7,9,11). In a retrospective review of patients with systemic symptoms related to cat scratch disease, Margileth concluded that rifampin, ciprofloxacin, trimethoprimsulfamethoxazole, and gentamicin were all potentially effective (8).…”
Section: Fig 1 Head Ct Demonstrating the Right Lateral Orbital Massmentioning
confidence: 99%